2016
DOI: 10.5137/1019-5149.jtn.17927-16.0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of polymorphisms of death pathway genes and mitochondrial pathway genes in intervertebral disc degeneration

Abstract: GG genotype of Bcl-2 gene may influence the level of its expression and may be effective on the development of IVDD. Additionally, expression of Bax gene may be related with different grades of IVDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Apoptosis of NPCs leads to downregulation of ECM synthesis by activating the p53 signaling pathway (Jin et al, 2018). Apoptosis is also involved in several grades of IVD degeneration (Eser et al, 2017). Other factors, such as nutrients and aging, may also regulate the viability of, and ECM synthesis by NPCs (Barakat et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis of NPCs leads to downregulation of ECM synthesis by activating the p53 signaling pathway (Jin et al, 2018). Apoptosis is also involved in several grades of IVD degeneration (Eser et al, 2017). Other factors, such as nutrients and aging, may also regulate the viability of, and ECM synthesis by NPCs (Barakat et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, autophagy caused by damaged mitochondria has a protective effect on cell apoptosis, suggesting a positive feedback mechanism under inflammatory stress conditions [93]. Eser et al [94] found a specific relationship between the Bcl-2 GG genotype and IDD, and the proportion of Bax-positive cells was associated with the IDD grade. Shang et al [95] also reported a relationship between the Bcl-2 gene polymorphism and IDD occurrence and severity.…”
Section: The Mitochondrial Pathway Induces Iddmentioning
confidence: 99%
“…Bax, Bcl-2, capsase-3, and caspase-9 are some important parameters to evaluate cell apoptosis [7][8][9]. Previously, lots of studies have reported an increase in the expression of apoptotic genes (Bax and caspase-3/9) and a decrease in the expression of antiapoptotic gene (Bcl-2) in patients with disc degeneration [10,11].…”
Section: Introductionmentioning
confidence: 99%